Apomixia como estratégia reprodutiva em Microlicia D. Don (Microlicieae, Melastomataceae) - Viana, Matheus Lacerda (2018)
Apomixis, asexual reproduction through seeds, is considered as a reproductive alternative for many angiosperms. In Melastomataceae, this mode of reproduction has been elucidated in Miconieae, although it is reported in other tribes, such as Microlicieae. Thus, this study used three species of Microlicia D. Don as model, Microlicia fasciculata Mart. ex Naudin, Microlicia polystemma Naudin and Microlicia sp. nov. in order to (i) verify the occurrence of apomixis in the studied species; (ii) verify if this mode of reproduction leads to the formation of polyembryonic seeds; (iii) investigate whether the apomic species present alterations during pollen grain development, with consequent pollen sterility, and (iv) investigate whether apomixis can occur in parallel to sexual process in the studied species. For this, we performed a test to detect autonomic apomixis, other to verify the presence of polyembryony, pollen viability analysis, pollen tubes growth analysis and the study of sporogenesis and gametogenesis by techniques used in anatomical studies. The three species were autonomous apomictic and presented polyembryonic seeds. The percentage of inviable pollen grains was high in M. fasciculata and M. polystemma, and total in M. sp. nov., due to meiotic abnormalities, symmetric mitosis and to the delay in the pollen development. The small formation of viable pollen grains and possible occurrence of natural pollination in M. fasciculata and M. polystemma allows sexual reproduction events, characterizing them as facultative apomictics. In M. sp. nov., the complete pollen sterility and the absence of evidence of natural pollination indicate obligatory apomixis. Although apomictic, all species retain stages of development that led to the formation of reduced embryo sacs. The independence of pollinators for fruit set, unipariental reproduction and polyembryonic seeds with embryos of different origins, can confer to these taxa reproductive flexibility and genetic diversity.